Sexual identities and lifestyles among non-heterosexual urban chiang mai youth: Implications for health - Arunrat Tangmunkongvorakul (2018)
Using quantitative and qualitative data we explore perspectives on and experiences of sexual lifestyles and relationships among more than 1750 young people aged 17-20 years who reside in urban Chiang Mai, Thailand. We focus on respondents' representations and understandings of their sexual/gender identities derived mainly from in-depth interviews and focus group discussions, supplemented with observations and field notes. Our results show that while many young Thais described themselves as heterosexual women or men, others described themselves as gay, kathoey, tom, dii, bisexual or something else. The terms gay, kathoey, tom and dii are commonly used by these Thais to denote a range of sexual/gender identities relating to persons who are sexually or romantically attracted to the same sex. We use case studies to illustrate the distinctive characterisations, sexual lifestyles and relationships of each of these identities, together with possible health implications. © 2010 Taylor & Francis.